Normothermic ex vivo liver perfusion: platform for liver graft assessment and therapeutic modification. (2nd October 2018) - Eymard, Corey; Markmann, James
ABSTRACT: Liver transplantation as a treatment for end stage liver failure remains limited in the United States by the number and quality of donor allografts. Static cold storage, the current standard of care for organ storage prior to transplantation, offers no method for assessment or therapeutic modification. Cold ischemia and its attendant hypoxia deplete cellular adenosine triphosphate (ATP) stores, promote cellular damage, and degrade overall organ quality. Normothermic ex vivo liver perfusion (NEVLP) offers the potential for assessment of allograft function and restoration of intracellular energy stores prior to transplantation. A completed phase III randomized trial demonstrated livers undergoing NEVLP prior to transplantation demonstrate superior early graft function and less early graft dysfunction. NEVLP offers a platform for modification of the allograft via the application of defatting or therapeutic cocktails, missense RNA technology, or gene editing modalities. The wide versatility of NEVLP appears to be a promising tool to expand the current pool of transplantable liver allografts.